2006
DOI: 10.1002/cphc.200600385
|View full text |Cite
|
Sign up to set email alerts
|

First Principles and Experimental 1H NMR Signatures of Solvated Ions: The Case of HCl(aq)

Abstract: A combined experimental and ab initio study is presented of the 1H NMR chemical shift distribution of aqueous hydrogen chloride solution as a function of acid concentration, based on Car-Parrinello molecular dynamics simulations and fully periodic NMR chemical-shift calculations. The agreement of computed and experimental spectra is very good. From first-principles calculations, we can show that the individual contributions of Eigen and Zundel ions, regular water molecules, and the chlorine solvation shell to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 61 publications
4
65
0
Order By: Relevance
“…Protons in the neighborhood of the triflate anion [121] should experience different shielding than what solvated protons far away from the anion experience. One expects in this case an overall up-field effect [122].…”
Section: Hydrated Proton Clusters Distribution In Acetonitrilementioning
confidence: 96%
See 1 more Smart Citation
“…Protons in the neighborhood of the triflate anion [121] should experience different shielding than what solvated protons far away from the anion experience. One expects in this case an overall up-field effect [122].…”
Section: Hydrated Proton Clusters Distribution In Acetonitrilementioning
confidence: 96%
“…The protonated water cluster should have exhibited more than one chemical shift due to the large chemical shifts of the hydrogen atoms which carry most of the proton charge as compared to the chemical shifts of protons further away from the protonated aqueous core. In particular, strongly hydrogen-bonded H-atoms like the H-atom shared (not necessarily equally) in between two neighboring water oxygen atoms should have exhibited down-field signals greater than δ 1 H = 20 ppm [122][123][124][125].…”
Section: Hydrated Proton Clusters Distribution In Acetonitrilementioning
confidence: 99%
“…Recently, a combination of NMR meaA C H T U N G T R E N N U N G surements with calculations in the frame work of such an ansatz was carried out by the Sebastiani group. [18] Similarly, experimental and calculated infrared spectra on HCl solvation were obtained by Uras-Aytemiz et al [19] First-principles simulations of the hydronium as well as the hydroxide ion dissolved in an ensemble of water molecules revealed that 60 % of the trajectory bears the solvated Eigen ion (H 9 O 4 + ), whereas in the remaining 40 % the hydronium ion takes the form of the Zundel cation. [5] The presence of both the Eigen as well as the Zundel cation is confirmed by Car-Parrinello simulations treating nuclear quantum effects.…”
mentioning
confidence: 99%
“…However, the integration of signals corresponding to the 20 CH 2 protons of the cyclohexyl rings increases from 20 in A and B to 28 in C, ruling out the assumption of the sulfur atom protonation. A possible interpretation is to consider that the peak at δ = 1.26-1.27 ppm may tentatively be assigned to the hydrogen atoms in water molecules solvating chloride ions, since according to Sebastiani et al [32] their NMR signals appear at lower-frequency values than those attributed to regular water (water in CDCl 3 appears at δ = 1.56 ppm [30]). Those investigators studied the ab initio and [20], was dissolved in deuterated chloroform, and the correspondent NMR spectrum plotted -see Fig.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 97%
“… Equilibrium results achieved upon the investigation of Pd(II) extraction by L in HCl / chloride media ranging from about 1.0 M to 4.5 M indicate that the extracted species have a 2:1 L:Pd(II) stoichiometry, one or two chloride ions are released from the coordination sphere of [PdCl 4 ] 2-in the aqueous media, with a minor participation of HCl in the Pd(II) extraction V=106.97+189.84 x DMDCHTDGA  UV-visible spectroscopic data show that [PdCl 4 ] 2-is not detected in the organic media after Pd(II) extraction from 1.5 M and 4.5 M HCl by L.  The 1 H NMR spectrum of a sample of L saturated with Pd(II), extracted from 4.5 M HCl, suggests chloride ions are present, but the signals of H 3 O + or H 5 O 2+ are not detectable[32]. Hence, this interpretation assumes the existence of LH + Cl -traces and L:Pd(II) species.…”
mentioning
confidence: 94%